Unbecoming Cinema Unsettling Encounters With Ethical Event Films - Fleming, David H. (Intellect, 2017)
Unbecoming Cinema constitutes a welcome addition to texts that provide a film-philosophical perspective on films that otherwise take on and involve difficult subject matter, including in this case suicide, autistic worldviews, hallucinatory aesthetics and vomit-gore. The book in effect argues successfully and intelligently that even though hard to watch, many of these films can provide for viewers an opportunity to come to a renewed understanding of self and world. As a result, the author takes on difficult topics, but brings them to life in an exciting, philosophical fashion that also asks readers to rethink what it is that constitutes cinema.